Influence of bioenergy on the Results of the forgotten and missed iss of the hockey teams of Russia and the USA on the Olympic Games in Pyeongchang - Sivakov, V. I.; Dolgova, V. I.; Kamskova, Y. G.; Matveeva, P. A.; Portnov, A. B. (International Journal of Applied Exercise Physiology, 2020)
Objective: to substantiate the bioenergy of the hockey teams of Russia and the USA on the result of goals scored and missed at the Olympic Games in Pyeongchang.